"The Other Dream" of Erewhon: an essay on the machines’ discreet rebellion (Colloquia Comparativa Litterarum, 2025)
This paper conducts a comparative analysis of Samuel Butler's seminal work, Erewhon: or, Over the Range, and Vladimir Poleganov's contemporary novel, The Other Dream. The analysis centers on the discreet influence exerted by technology in the pursuit of territorial survival. The study delves into the catastrophic consequences arising from both the success and failure of this technological endeavour.
Keywords: artificial intelligence; machine rebellion; pace and territory